Counsellor Stress in the Field of Trauma - Arvay, Marla J.; Uhlemann, Max R. (Canadian Journal of Counselling and Psychotherapy, 2007)
A survey research design was used to study levels of stress among a random sample of counselors (N=161) working in the field of trauma in British Columbia. Counsellors were assessed on measures of general life stress, burnout, and traumatic stress. Twenty-four percent were experiencing high levels of general life stress, 16% reported high levels of Emotional Exhaustion, 26% felt ineffective in terms of Personal Accomplishment at work, and 14% were experiencing high traumatic stress levels similar to clients with post-traumatic stress disorder. Relationships between measures and demographic variables are presented, and a profile of impaired counselors was identified. Implications of these findings for counsellors working with trauma victims are discussed.